COMPARISON OF RADIOGRAPHIC METHODS AND COMPUTED TOMOGRAPHY SCANOGRAMS FOR MEASURING LEG LENGTH DISCREPANCIES - TRIVITAYARATANA, Wanna; TRIVITAYARATANA, Pichit; VONGSABARN, Chavalit; NUKROO, Songthip (The ASEAN Journal of Radiology, 2023)
Four radiographic methods for measuring leg length discrepancies were compared to computed tomography (CT) scanograms by exposing a polyvinyl chloride (PVC) phantom. Central ray of X-ray machine was checked. At 180 cm focal film distance (FFD), the elongation error at hip, knee and ankle joints of teleroentgenography(except knee joint), teleroentgenography mixed with orthoroentgenography, orthoroentgenography, spot orthoroentgenography and CT scanograms were 20, 5, 0, 0 and 0 mm, respectively. Although the elongation error was found in the first two methods, the whole leg length could be visualized in single exposure radiograph. No elongation error occured in orthoroentgenography, spot orthoroentgenography because of the central ray centered directly over the three joints of lower limb, but they had several disadvantages. Three separate roentgenograms were needed and entired leg pathology could not be seen on one radiograph. CT scanograms was the most accurate and was the standard method for leg length measurement. However, this technique was more expensive and needed more time to complete an examination than the radiographic JAN. - APR. 1999. Volume V Number I methods.